Predicting solvent effects on the structure of porous organic molecules - Jelfs,KE; Santolini,V; Tribello,GA (Chemical Communications, 2015)
A computational approach for the prediction of the open, metastable, conformations of porous organic molecules in the presence of solvent is developed.